Enhancing Beauty with Botox: A Maqasid al-Shari'ah Perspective - Rahma Hanim Azzahra; Qurrota A’yun; Musyafa'ah, Nur Lailatul; Gatralina Sekar Harum Ael Yanda (Nurani, 2024)
Many women employ various methods to enhance their beauty and attractiveness, with Botox being a popular choice. Consequently, numerous beauty clinics now offer Botox therapy, despite its potential side effects. This article aims to explore Botox therapy for beauty from the perspective of maqasid al-shari’ah. The study was conducted at a beauty clinic (referred to as XD) using field research methods, including interviews and literature review. Data were analyzed descriptively through the lens of maqasid al-shari’ah. The study found that Botox therapy at the XD clinic is used to address health issues, particularly those related to muscle failure. Additionally, it is utilized for aesthetic purposes, such as reducing facial wrinkles. However, frequent or improperly performed Botox treatments can pose risks to patients. From the perspective of maqasid al-shari’ah, Botox use is closely linked to the preservation of life (hifz al-nafs). Thus, Botox can be considered permissible (mubah), especially for medical reasons. For purely cosmetic purposes without medical necessity, it is deemed undesirable (makruh). It is crucial that Botox procedures are performed by qualified professionals.